The ferromagnetic behaviour of conducting polymers revisited - Nascimento, O. R.; de Oliveira, A. J. A.; Pereira, E. C.; Correa, A. A.; Walmsley, L. [UNESP] (Iop Publishing Ltd, 2008)
The magnetic properties of doped pellets of poly(3-methylthiophene) showing room temperature ferromagnetic behaviour have been discussed in a previous article. The magnetic behaviour was attributed to a weak ferromagnetic phase, due to the superexchange interaction of polarons via the dopant anions. The Dzialoshinsky-Morya interaction among canted spins was proposed to explain the ferromagnetism. In this article the main conclusions of that work concerning the magnetic behaviour are revised. The basic assumption now is that the magnetic moments are spin 1/2 polarons that can interact antiferromagnetically and/or ferromagnetically. In the small crystalline regions of the polymer, which are identified with the polymer portion that remains ferromagnetic at room temperature, the interaction gives rise to S = 0 and 1 bipolarons and the S = 1 triplet state is lower in energy. In the disordered region, disorder will prevent the complete S = 1 and 0 coupling and bands of polarons ferromagnetically and antiferromagnetically coupled will appear. Using this approach, all the magnetization data can be qualitatively explained, as well as the electron spin resonance data.